2006
DOI: 10.1111/j.0307-6946.2006.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of arthropod predators to Cry1Ab toxin in Bt maize fields

Abstract: Abstract.  1. To assess the risks of an insect‐resistant transgenic plant for non‐target arthropods, it is important to investigate the exposure of non‐target species to the transgene product. Exposure of predators in the field depends on the toxin levels in food sources, their feeding ecology and that of their prey.2. To verify the transmission of Cry1Ab toxin through the food chain, and thus exposure of predators in the field, samples from different plant tissues, herbivores, and predators in Bt maize fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
135
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(146 citation statements)
references
References 43 publications
9
135
1
1
Order By: Relevance
“…Numerous potential prey species for spiders tested positive for Bt-endotoxins from the field, including several beetles (Coleoptera), true bugs (Hemiptera), moth larvae (Lepidoptera: Noctuidae), adult and nymphal crickets (Orthoptera: Gryllidae), harvestmen (Opiliones), millipedes (Diplopoda: Julida), centipedes (Chilopoda: Lithobiomorpha, Geophilomorpha), and earthworms (Haplotaxida: Lumbricidae) (Table S2). Previous studies have also shown clear evidence for the uptake of Cry1Ab Bt-endotoxins from transgenic corn by potential prey items, including corn flea beetle Chaetocnema pulicaria (Coleoptera: Chrysomelidae), Japanese beetle Popillia japonica (Newman) (Coleoptera: Scarabaeidae), pink spotted lady beetle Coleomegilla maculata (DeGeer) (Coleoptera: Coccinellidae), and damsel bug Nabis roseipennis Reuter (Hemiptera: Nabidae) (Harwood et al, 2005(Harwood et al, , 2007Obrist et al, 2006;Wei et al, 2008;Zwahlen & Andow, 2005). These studies, as well as our own, found a large degree of variation in the uptake of Cry proteins by different prey species (see Table S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous potential prey species for spiders tested positive for Bt-endotoxins from the field, including several beetles (Coleoptera), true bugs (Hemiptera), moth larvae (Lepidoptera: Noctuidae), adult and nymphal crickets (Orthoptera: Gryllidae), harvestmen (Opiliones), millipedes (Diplopoda: Julida), centipedes (Chilopoda: Lithobiomorpha, Geophilomorpha), and earthworms (Haplotaxida: Lumbricidae) (Table S2). Previous studies have also shown clear evidence for the uptake of Cry1Ab Bt-endotoxins from transgenic corn by potential prey items, including corn flea beetle Chaetocnema pulicaria (Coleoptera: Chrysomelidae), Japanese beetle Popillia japonica (Newman) (Coleoptera: Scarabaeidae), pink spotted lady beetle Coleomegilla maculata (DeGeer) (Coleoptera: Coccinellidae), and damsel bug Nabis roseipennis Reuter (Hemiptera: Nabidae) (Harwood et al, 2005(Harwood et al, , 2007Obrist et al, 2006;Wei et al, 2008;Zwahlen & Andow, 2005). These studies, as well as our own, found a large degree of variation in the uptake of Cry proteins by different prey species (see Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Techniques using monoclonal and/or polyclonal antibodies, such as enzyme-linked immunosorbent assay (ELISA), have been successfully employed to detect the presence of Bt-endotoxins in field-collected arthropods, such as Coleoptera (Harwood et al 2005(Harwood et al , 2007Peterson et al 2009;Zwahlen & Andow 2005), Acari (Obrist et al 2006;Torres & Ruberson 2008), and Araneae (Harwood et al 2005). Ahmad et al (2005) measured ground-dwelling arthropod abundance (including spiders) and, in parallel, used ELISA to quantify Bt-endotoxin concentration in the soil, but did not test for the uptake of proteins by the arthropods themselves.…”
Section: Introductionmentioning
confidence: 99%
“…For risk assessment, one may wish to know the highest concentration of a substance that elicits no adverse effect on an organism; this is the no observable adverse effect concentration or NOAEC. If no organism were Raybould et al 2007 3 E.g., Head et al 2001;Raps et al 2001;Dutton et al 2002;Howald et al 2003;Obrist et al 2005;Obrist et al 2006a;Obrist et al 2006b;Torres et al 20064 Babendreier et al 2004 5 Westgate et al 2003;Depuis et al 1987 6 E.g., Khan & Afzal 1950;Thies 1953;Sidhu & Singh 1961;Llewelyn & Fitt 19967 Crocker et al 2002 exposed to concentrations of a substance greater than its NOAEC, then that substance would pose minimal risk to non-target organisms. Thus a third hypothesis can be tested to determine the safety of exposure to a transgenic protein, or to any other potential toxin detected in a GM crop:…”
Section: Cropsmentioning
confidence: 99%
“…The predatory mite Neoseiulus californicus McGregor (Acari: Phytoseiidae) feeds on mites of the family Tetranychidae (McMurtry and Croft, 1997) and can acquire the Cry protein by ingesting T. urticae mites that feed on Bt plants (Dutton et al, 2002;Obrist et al, 2006 (Figure 1a). The results were positive with Bt maize leaf discs samples (30F35 Hx), in which a second test line was developed in the region between the control line and the lower end of the strip.…”
mentioning
confidence: 99%